Setting the scientific stage for esports psychology: a systematic review. Issue 1 (1st January 2020) - Pedraza-Ramirez, Ismael; Musculus, Lisa; Raab, Markus; Laborde, Sylvain
ABSTRACT: Competitive gaming, better known as electronic sports (esports), is rapidly growing in popularity. We systematically reviewed the available literature regarding the psychological aspects of esports using the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) evidence-based reporting checklist and a Population, Intervention, Comparator, and Outcomes (PICO) framework with the following inclusion criteria: (i) published between 1994 and 2018; (ii) empirical investigation (as the current state of research is dense with positions and opinions but has few empirical investigations); and (iii) focussed on esports games that are associated with either cognitive performance or game performance. The goal of our research was twofold: to present a summary of the empirical evidence addressing the psychological characteristics of both cognitive and game performance in esports, and to integrate esports in the field of sport psychology. More specifically, our goals were to highlight the interplay of psychological aspects of performance and esports and to clearly define the theoretical foundations of the psychological aspects of esports performance. Underlining the differences from video gaming will inform future research directions and stimulate the development of high-quality practice in the applied field of sports and exercise psychology.